Formylation of metallocomplexes of p- and m-tetraanizylporphyrins - S. V. Tsukanov; V. D. Rumyantseva; A. F. Mironov (Тонкие химические технологии)
The Vilsmeyer formylation reaction a of metallocomplexes of m- and p- methoxy-substituted tetraphenylporphyrins was investigated. Formyl derivatives of m-isomers were shown to form cyclization products not only in solutions but in solid state. Ability to such transformations decreases in a number Co>Cu>Ni>Pd>Pt.